2017
DOI: 10.1038/s41598-017-03155-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of JAZ gene family in upland cotton (Gossypium hirsutum)

Abstract: Plant JAZ (Jasmonate ZIM-domain) proteins play versatile roles in multiple aspects of plant development and defense. However, little is known about the JAZ family in allotetraploid upland cotton (Gossypium hirsutum) so far. In this study, 30 non-redundant JAZ genes were identified in upland cotton through genome-wide screening. Phylogenetic analysis revealed that the 30 proteins in cotton JAZ family are further divided into five groups (I – V), and members in the same group share highly conserved motif structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
4
17
0
Order By: Relevance
“…The number and length of exon and intron showed great variations in CsJAZ genes. This finding was consistent with the JAZ genes of other plants, such as upland cotton and wheat [10,15]. The structure variations of JAZ genes might be caused by structural divergence mechanisms, such as the insertion or deletion of the exons and introns proposed by Xu et al [32].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The number and length of exon and intron showed great variations in CsJAZ genes. This finding was consistent with the JAZ genes of other plants, such as upland cotton and wheat [10,15]. The structure variations of JAZ genes might be caused by structural divergence mechanisms, such as the insertion or deletion of the exons and introns proposed by Xu et al [32].…”
Section: Discussionsupporting
confidence: 89%
“…In wheat, TaJAZ6 and 13 were specifically expressed in root, and the expression level of TaJAZ3 in root tissues was as high as that in stamen [10]. GhJAZ1-A/D, GhJAZ3-A/D, GhJAZ5-A/D, and GhJAZ13-A/D in the upland cotton also showed higher expression in roots than in stems or leaves [15]. These results indicated that CsJAZ genes might exert certain functions as SmJAZ1 and SmJAZ2 [36] in roots and maintain the normal development of tea plants under normal conditions.…”
Section: Discussionmentioning
confidence: 92%
“…The released MYC in turn activates the transcription of JAZ (Zhang et al, 2015). The JAZ proteins are a subgroup of the TIFY family, characterized by the N-terminal located ZIM domain and the C-terminal located Jas domain (Thines et al, 2007; Melotto et al, 2008; Li et al, 2017). The ZIM domain, which consists of 30 amino acids with a highly conserved TIFY motif (TIF[F/Y]XG), is required for the formation of homo- and hetero-dimers within the JAZ proteins (Vanholme et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cis-elements located in the promoter region of genes play key roles in the developmental and environmental regulation of gene expression [42]. According to cis-element analysis, the promoter regions of Gh4CL genes possess elements related to stress responses, such as ABRE, TC-rich, LTR, MBS, TGA-element, TCA-element, CGTCA-motif and TGACG-motif [43][44][45][46], suggesting a potential role of the Gh4CL genes with these cis-element(s) in tolerance of stresses, such as drought, salt, heat, ABA, and low temperature.…”
Section: Discussionmentioning
confidence: 99%